Peran Tokoh Agama Dalam Peningkatan Pemahaman Agama Masyarakat Kampung Toweren Aceh Tengah - Karimi Toweren (Universitas Islam Negeri Ar-Raniry Banda Aceh, Aceh, Indonesia., 2018)
Religious figures have an important role in increasing society’s religious understanding, so that it may behave and comply with the proper guidelines and teachings of Islam. An issue apparent in Toweren Village was that many of its population who kept dogs without observing shariah guidelines and understanding the proper concept of mughallazahnajs. The purposes of this research were: (1) the efforts exerted by the religious figures, (2) impeding factors, (3) and problem-solving solutions on the issue of increasing the religious understanding of the community members of Toweren Village, Lut Tawar District, Central Aceh Regency regarding mughallazahnajs on the context of dog keeping. It is a descriptive qualitative research, and data was collected through interview and observation. The research results indicated that: (1) the efforts exerted by the religious figures were only limited to general activities within the community, such as Friday prayer, teaching of village apparatus’ wives on Friday morning, reciting yasin on Thursday night, teaching of district officials every fifteenth of the month, giving advice during a wake, and doing announcements using the mosque’s loudspeaker; (2) impeding factors, comprising: (a) internal factors, such as education background and the difference in characters among the community members, and (b) external factors, such as the limitedness of energy, time, fund, facility, media, and fiqh-studying programs, as well as a lack ofcoordination between religious figures and relevant government agencies; (3) solutions to be implemented included: (a) increasing the frequency of fiqh studies, (b) intense socialization of fiqh studying on the mughallazahnajs concept, (c) conducting a shariah-complying village program, (e) forming a special team to handle the problems faced by dog-keeping community members, and (f) cooperating with the village apparatus and district/regency religious agencies to treat this case as a top priority.